Great Powers, Small Wars Asymmetric Conflict since 1945 - Deriglazova, Larisa (Johns Hopkins University Press, 2014)
A sophisticated appraisal of the problem of asymmetric conflict in the post-World War II period.In a sophisticated combination of quantitative research and two in-depth case studies, Larisa Deriglazova surveys armed conflicts post World War II in which one power is much stronger than the other. She then focuses on the experiences of British decolonization after World War II and the United States in the 2003 Iraq war. Great Powers, Small Wars employs several large databases to identify basic characteristics and variables of wars between enemies of disproportionate power. Case studies examine the economics, domestic politics, and international factors that ultimately shaped military events more than military capacity and strategy.